2004
DOI: 10.1016/j.bulm.2003.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Competition and natural selection in a mathematical model of cancer

Abstract: A malignant tumor is a dynamic amalgamation of various cell phenotypes, both cancerous (parenchyma) and healthy (stroma). These diverse cells compete over resources as well as cooperate to maintain tumor viability. Therefore, tumors are both an ecological community and an integrated tissue. An understanding of how natural selection operates in this unique ecological context should expose unappreciated vulnerabilities shared by all cancers. In this study I address natural selection's role in tumor evolution by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
77
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 35 publications
2
77
1
Order By: Relevance
“…As tumors enlarge, and develop or recruit vascular tissue, they can become more heterogeneous both genetically and phenotypically [22], comprising a mix of cancerous and healthy cell types that cooperate as an integrated tissue but also compete for food and space. Nagy [23] developed an evolutionary ecological model that incorporated tumor heterogeneity and showed that interactions in such cellular communities could lead to competitive exclusion of cell lineages, in some situations giving rise to 'hypertumors' that exploit the developed vasculature to grow more quickly than do other cancer cell clones, but then die because they do not have a capacity to support further angiogenesis. He described how indirect evidence from the histology of some cancers supports the existence of hypertumors, and how the evolved balance between cooperation and competition in tumors has crucial clinical implications for optimizing cancer therapies.…”
Section: Reviewmentioning
confidence: 99%
“…As tumors enlarge, and develop or recruit vascular tissue, they can become more heterogeneous both genetically and phenotypically [22], comprising a mix of cancerous and healthy cell types that cooperate as an integrated tissue but also compete for food and space. Nagy [23] developed an evolutionary ecological model that incorporated tumor heterogeneity and showed that interactions in such cellular communities could lead to competitive exclusion of cell lineages, in some situations giving rise to 'hypertumors' that exploit the developed vasculature to grow more quickly than do other cancer cell clones, but then die because they do not have a capacity to support further angiogenesis. He described how indirect evidence from the histology of some cancers supports the existence of hypertumors, and how the evolved balance between cooperation and competition in tumors has crucial clinical implications for optimizing cancer therapies.…”
Section: Reviewmentioning
confidence: 99%
“…To study the GRH's application to cancer in more detail, I modified an existing simple model of vascular tumor growth [6] to include P demand. Let P (t), x(t), y(t) and z(t) be intracellular [P], tumor parenchymal cell mass, vascular endothelial cell mass, and microvessel length density, respectively at time t. Assume interstitial [P] is a function of microvessel density v = z/x of the form P e = v/(a+v).…”
mentioning
confidence: 99%
“…Phosphate leaks from cells at constant per unit cell mass rate l. Phosphate from dying cells is returned to the interstitial fluid. The per unit mass growth rate of tumor cells is assumed to be governed by an equation of the form (adapted from [6]),…”
mentioning
confidence: 99%
See 2 more Smart Citations